2023
DOI: 10.3390/foods12122317
|View full text |Cite
|
Sign up to set email alerts
|

Pungency Perception and the Interaction with Basic Taste Sensations: An Overview

Abstract: The perception of pungency can be attributed to the combination of pain and heat, and it has critical impacts on food flavor and food consumption preferences. Many studies have reported a variety of pungent ingredients with different Scoville heat units (SHU), and the mechanism of pungent perception was revealed in vivo and in vitro. The worldwide use of spices containing pungent ingredients has led to an increasing awareness of their effects on basic tastes. However, the interaction between basic tastes and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 163 publications
0
3
0
Order By: Relevance
“…Further analysis showed that the positive effect of numbing-spicy avor on GWG was partially mediated by TD and MD. Unlike the simple spicy avor found in other Chinese cuisines, the Mala evoked by Chinese prickly ash combined with chili peppers constitutes the distinctive feature of Sichuan cuisine (32). This Mala sensation in the mouth further affect the mediation and recognition of tastes, stimulating appetite.…”
Section: Discussionmentioning
confidence: 92%
“…Further analysis showed that the positive effect of numbing-spicy avor on GWG was partially mediated by TD and MD. Unlike the simple spicy avor found in other Chinese cuisines, the Mala evoked by Chinese prickly ash combined with chili peppers constitutes the distinctive feature of Sichuan cuisine (32). This Mala sensation in the mouth further affect the mediation and recognition of tastes, stimulating appetite.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, upon stimulation of the oral cavity by foreign substances, the human body integrates signals and may release endorphins, thereby heightening sensitivity to taste and odor and enhancing salty taste perception. For instance, capsaicin was found to enhance responses in the cerebral cortex and OFC to high-salt stimulation, indicating the central role of the trigeminal nerve in salty taste perception [ 93 , 94 ].…”
Section: Detailed Multisensory Synergistic Effectmentioning
confidence: 99%
“…In addition, spiciness is not considered as a taste or flavor in the traditional concept. Certain substances, such as capsaicin, elicit the sensation in question, which interacts with receptors located in the oral cavity and on the tongue . The experience of spiciness is classified as chemesthetic perception, indicating its association with chemical senses rather than fundamental tastes, such as sweetness, saltiness, sourness, bitterness, and umami .…”
Section: Introductionmentioning
confidence: 99%